Prediction of Electric Car Mileage Using Taylor Series Based on Power Consumption, Speed, and Road Conditions - Nasution, Afifah Naila; Alvansyah, Oka; Imelda, Yusmita; Sitepu, Ahmad Denil; Harliana, Putri (CV. Rayyan Dwi Bharata, 2025)
This research aims to predict the range of electric vehicles using the Taylor Series method based on power consumption, speed, and road conditions. Data were collected from various electric vehicle brands with full and half battery capacities, using a speed of 60 km/h on flat, uphill, and downhill roads. The research method involved mathematical modeling with the Taylor Series, implemented using MATLAB. The results indicate that road conditions affect power consumption, with the highest range achieved on downhill roads and the lowest on uphill roads. Vehicles with larger battery capacities recorded longer ranges. The study concludes that the Taylor Series can accurately predict the range of electric vehicles, assisting users in better travel planning.